Handball playing volume and knee injury risk in youth handball: the influence of sex - Møller, M.; Myklebust, G.; Möller, S.; Wedderkopp, N.; Lind, M.; Nielsen, R. O. (Journal of Science and Medicine in Sport, 2025)
Objectives To investigate if sex modifies the association between change in weekly handball volume and knee injury risk in youth handball players.